SUPPLY CHAIN MANAGEMENT ON COMPETENCY EXCELLENCE AND ORGANIZATIONAL PERFORMANCE OF RETAIL COMPANIES PT. SUMBER ALFARIA TRIJAYA TBK SOUTH KALIMANTAN - Firdaus Firdaus (SEAN Institute, 2023)
This research highlights the importance of supply chain management (SCM) and competency excellence in improving organizational performance. In the context of PT. Sumber Alfaria Trijaya Tbk in South Kalimantan found that SCM plays a crucial role in influencing organizational performance and building superior company competency. The research results show that SCM has a positive and significant influence on the company's organizational performance. This confirms that efforts to improve supply chain management can result in significant performance improvements. Apart from that, SCM also has a positive and significant influence on the company's competency excellence. This emphasizes the importance of effective integration of SCM in a company's business strategy to build competitive advantage. Research findings also reveal that competency excellence has a significant positive impact on organizational performance. This shows that companies that are able to build and maintain competitive advantages in the industry have the potential for better performance. Furthermore, this research reveals that competency excellence acts as a mediator between SCM and organizational performance. In other words, effective supply chain management can help companies build competitive advantages, which in turn improves organizational performance.